Multilinear Singular Integral Operators on Generalized Weighted Morrey Spaces. (17th July 2014) - Hu, Yue; Li, Zhang; Wang, Yueshan
Abstract : The purpose of this paper is to discuss the boundedness properties of multilinear Calderón-Zygmund operator and its commutator on the generalized weighted Morrey spaces.